2006
DOI: 10.1158/1535-7163.mct-05-0367
|View full text |Cite
|
Sign up to set email alerts
|

The cardenolide UNBS1450 is able to deactivate nuclear factor κB–mediated cytoprotective effects in human non–small cell lung cancer cells

Abstract: Non -small cell lung cancers (NSCLC) are associated with very dismal prognoses, and adjuvant chemotherapy, including irinotecan, taxanes, platin, and Vinca alkaloid derivatives, offers patients only slight clinical benefits. Part of the chemoresistance of NSCLCs results from the constitutive or anticancer drug-induced activation of the nuclear factor-KB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 48 publications
3
60
0
1
Order By: Relevance
“…The overall growth levels of the human cancer cell lines were determined using the colorimetric MTT [3-(4,5-dimethylthiazol-2yl)]-diphenyltetrazolium bromide, Sigma, Belgium) assay (12)(13)(14)(15)(16)(17). Briefly, cell lines were incubated for 24 h in 96-microwell plates at concentrations of 10,000-40,000 cells/ml, depending on the cell type, to ensure adequate plating prior to making cell growth determinations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall growth levels of the human cancer cell lines were determined using the colorimetric MTT [3-(4,5-dimethylthiazol-2yl)]-diphenyltetrazolium bromide, Sigma, Belgium) assay (12)(13)(14)(15)(16)(17). Briefly, cell lines were incubated for 24 h in 96-microwell plates at concentrations of 10,000-40,000 cells/ml, depending on the cell type, to ensure adequate plating prior to making cell growth determinations.…”
Section: Methodsmentioning
confidence: 99%
“…The number of living cells after 72 h of culture in the presence (or absence for the negative control) of the various compounds was directly proportional to the intensity of the blue colour, which was measured quantitatively by spectrophotometry using a Bio-Rad Model 680XR (Bio-Rad, Nazareth, Belgium) at the 570-nm wavelength (with a reference wavelength of 630 nm). Each experimental condition was run six times (12)(13)(14)(15)(16)(17). Quercetin was obtained from Sigma (Bornem, Belgium), and quercetin-3-O-glucuronide (miquelianin) and quercetin-3-Ogalactoside (hyperoside) were obtained from Carbosynth (Compton, Berkshire, England).…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of reports document the ability of some CS to circumvent cancer cell chemoresistance [50][51][52][53][54], making them an interesting starting point for the development of new anti-chemoresistance treatment strategies.…”
Section: Cardiotonic Steroidsmentioning
confidence: 99%
“…Many tumour cells display constitutively high levels of nuclear NF-κB activity due to the hyperactivation of the NF-κB signalling pathways or to inactivating mutations in the regulatory Iκ-B subunits [76][77][78]. Several CS have already been shown to interfere with the NF-κB pathway [51,[79][80][81]. We previously reported that 19-hydroxy-2′′-oxovoruscharin (UNBS1450) is able to sensitise chemoresistant, highly aggressive, and naturally therapy-resistant A549 NSCLC cancer cells by deactivating the cytoprotective effects caused by constitutively activated NF-κB [51].…”
mentioning
confidence: 99%
See 1 more Smart Citation